Factors Affecting Change Management in Public Organizations in Bangladesh - A. K. Mahbubul Hye; Mahadi Hasan Miraz; Md. Mamun Habib (International Journal of Supply Chain Management, 2020)
Purpose-The study explore the various facets of different wave retail banking models including their merits, demerits are security issues, to share the wave retail wave banking implementation in Bangladesh. To evaluate the current status and preparedness of banks to facilitate wave retail banking in Bangladesh. To developed smooth operation and implementation of wave retail banking in Bangladesh. Scope: Renown Banks in Bangladesh. Significance: This trend contributes towards the anticipated growth of wave financial information services, funds transfer, bill payment and presentation, account management and customer service solutions. Theory: Unified Theory of Acceptance and Use of Technology (UTAUT). Method: To conduct the study primary as well as secondary data have been collected 100 users of bank account holder in Dhaka city were interviewed to know about their interest about cashless wave banking in retail market. Tools: SPSS for pilot test and PLS for data analysis. Findings: the elaborate the current wave retail executing infrastructure of Bangladesh and understand the awareness and readiness of customers satisfaction regarding wave retail banking in retail market supply chain management. Originality: This is one of the most recent research studies has made on the retail weave in Bangladesh. Keywords: Wave retail banking, Trend contribution, Wave retail banking facts, Supply Chain Management.